Nazi terror : the Gestapo, Jews, and ordinary Germans - Johnson, Eric Arthur 1948- (Basic Books, 2000)
"Central argument is this: the Nazis did not rule by terror and terror rarely touched the lives of most ordinary Germans. The terror apparatus at the dark heart of Nazi Germany, set in motion by the Nazi Party leadership in Berlin, employed a selective terror that concentrated almost exclusively on Jews and other specifically targeted enemies of the Nazi regime. It depended for its implementation and effectiveness, however, on the cooperation and often voluntary participation at the local level of the broad mass of ordinary German citizens who themselves suffered little or not at all from Nazi terror." -- Jacket